Critical role for heat shock protein 20 (HSP20) in migration of malarial sporozoites - Montagna, Georgina N.; Münter, Sylvia; Frischknecht, Friedrich (The journal of biological chemistry, 2012)
Plasmodium sporozoites, single cell eukaryotic pathogens, use their own actin/myosin-based motor machinery for life cycle progression, which includes forward locomotion, penetration of cellular barriers, and invasion of target cells. To display fast gliding motility, the parasite uses a high turnover of actin polymerization and adhesion sites. Paradoxically, only a few classic actin regulatory proteins appear to be encoded in the Plasmodium genome. Small heat shock proteins have been associated with cytoskeleton modulation in various biological processes. In this study, we identify HSP20 as a novel player in Plasmodium motility and provide molecular genetics evidence for a critical role of a small heat shock protein in cell traction and motility. We demonstrate that HSP20 ablation profoundly affects sporozoite-substrate adhesion, which translates into aberrant speed and directionality in vitro. Loss of HSP20 function impairs migration in the host, an important sporozoite trait required to find a blood vessel and reach the liver after being deposited in the skin by the mosquito. Our study also shows that fast locomotion of sporozoites is crucial during natural malaria transmission.
First Published: December 2, 2011
Gesehen am 26.04.2018